Issues of justice and reconciliation in complex political emergencies conceptualising reconciliation, justice and peace - Pankhurst, Donna (1999)
This paper focuses on what can be done during emergency and transition periods to promote sustainable peace, in the aftermath of complex political emergencies in Africa, with particular reference to issues of reconciliation and justice. There is no common understanding of the political conditions under which efforts at reconciliation should be minimal in relation to a focus on justice in order to achieve the 'best' peace, or of those where the pursuit of justice should become paramount. There is also not even a common language of what justice and reconciliation mean in the context of post-conflict peace-building. The paper concludes that there is a much greater potential role for outsiders with regard to justice, while reconciliation is considered to be more of an internal affair in which international actors can only be present as supporters of domestic initiatives, and even then with great caution.